Health-related quality of life in sepsis survivors - Laura Menezes Silveira; Carina Aparecida Marosti Dessotte; Rosana Aparecida Spadoti Dantas; Matheus Rozário Matioli; Angelita Maria Stabile (Universidade Federal do Ceará, 2015)
Objective: to identify the evidence available on the changes in health-related quality of life of patients who survived an episode of sepsis. Methods: the LILACS, MEDLINE CINAHL Cochrane Library, Web of Science and Scopus databases were used. Results: of the 1729 publications identified, 16 were included in the study. Patients who survived an episode of sepsis presented reduction in the quality of life when compared to the general population or to other groups of patients who had an episode of severe illness, even after long periods following discharge from hospital, independently of the scale used, of the patients' clinical characteristics, and their country of origin. The changes in the quality of life are mainly related to the physical and mental aspects. Conclusion: knowledge of the changes in quality of life of patients who survived an episode of sepsis demonstrates the need for long-term monitoring of these patients.